Innovative management practices for sustainable growth in China’s private enterprises: Challenges and solutions - Zhang, Zhilin; Wang, Zhijian; Han, Wenyuan; Cui, Xin (Edelweiss Applied Science and Technology, 2025)
As China’s private enterprises increasingly drive the nation’s economy, effective management of performance is essential for ensuring their sustainability and competitive edge. This paper explores the critical challenges faced by private enterprises in China regarding performance management, highlighting gaps in their systems that hinder long-term growth. Despite their pivotal role in generating over 60% of the country’s GDP, private enterprises frequently encounter problems such as poor leadership understanding, insufficient performance evaluation metrics, and ineffective employee engagement strategies. Through a comprehensive literature review, this study emphasizes the importance of adopting innovative performance management practices that integrate modern HRM techniques with strategic business planning. The research aims to provide practical solutions to enhance productivity, employee retention, and overall organizational performance within the private sector, driving them toward sustainable development.